Soft tissue healing with and without osseous recontouring - (:unkn) unknown (My University, 1990)
The purpose of this investigation was to examine the differences in soft tissue healing after treatment with osseous recontouring and flap curettage. A total of fifteen patients who had adult periodontitis and demonstrated bilaterally similar periodontal destruction participated in the study. After the initial examination, they received instruction in oral hygiene and had their teeth thoroughly scaled and root-planed. The posterior segments of these patients were then treated with osseous recontouring or flap curettage. Following treatment, the patients were recalled every 4 weeks for professional tooth cleaning. Post operative measurements were made at the sixth month. The results demonstrated that osseous recontouring and flap curettage equally reduced plaque and gingival inflammation. Although, osseous recontouring caused loss of attachment at the facial and lingual surfaces, probing attachment gain at the approximal surfaces in both treatment groups had occurred but this was limited (0.5 mm) and there was no difference statistically between the two groups. Pocket reduction was achieved in both treatment modalities and differences in the two groups were statistically significant. At the sixth month, it was also observed that, a better post operative morphology of the gingiva had occurred on the side subjected to osseous recontouring.
Keywords: Adult; Humans; Middle Aged; Periodontics; Surgical Flaps; Tooth Root; Alveolar Bone Loss; Wound Healing; Periodontal Index; Periodontitis; Subgingival Curettage; Epithelial Attachment